PREVALENSI MALARIA PADA DAERAH ENDEMIS ORANG RIMBA PROVINSI JAMBI MENGGUNAKAN PEMERIKSAAN MIKROSKOPIS - Ade Suryaman; Chairil Anwar; Dwi Handayani; Sulfa Esi Warni; Irsan Saleh; Dalillah Dalillah; Gita Dwi Prasasty (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2020)
Background: Malaria remain a world health problem with the highest number of case are in tropic and subtropic country such as Indonesia. Orang Rimba is a native tribe living secluded deep in the Taman Nasional Bukit Duabelas Forest and in the northern area were living in the Taman Nasional Bukit Tigapuluh. For demography, tteh were unregistered due to the difficulties of the survey, since they were living nomaden. Lack of transportation, living deep in the forest, low education level, bad living environment and low social economic level affect the risk of Malaria case number. This research amied to identifiy the prevalence of Malaria on endemic location of orang rimba in jambi province using microscopic examination. Methods: This was a descriptive observational study. The population in this study were all communities of Anak Rimba. A total of 94 Anak Rimba were recruited for the study.Malaria status were checked using gold standar which is Microscopical examination of the blood smear. Results: The results showed that 4,95% of the respondents were positive Malaria with plasmodium vivax (3,96%) and 0,99% special falciparum Conclusion: There were high prevalence of Malaria on Anak Rimba at Sungaiterap Desa Jelutih, Kec. Batin XXIV, Kabupaten Batangahari, Provinsi Jambi